2010
DOI: 10.1590/s2179-975x2010000200001
|View full text |Cite
|
Sign up to set email alerts
|

The fate of Eichhornia azurea (Sw.) Kunth. detritus within a tropical reservoir

Abstract: Aim: This study is aimed at comparing the kinetics of decomposition of Eichhornia azurea and discussing the fate of its detritus; Methods: The samples of aquatic macrophytes and water were collected in the Piraju Reservoir (São Paulo State, Brazil). The plant material was oven-dried and triturated and for each experimental condition (aerobic and anaerobic), 72 mineralization chambers were prepared with plant fragments and reservoir water. On sampling days the particulate and dissolved organic matter were quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Analysis of the percent mass loss of E. azurea observed in this study reveals that its decomposition ratio was very slow in comparison to others reported in the literature (Pagioro and Thomaz 1998, Stripari and Henry 2002, Padial and Thomaz 2006, Martins et al 2011, Bianchini Jr. et al 2014. In contrast, the half-life (t 1/2 = 468 days) calculated up to the 35 th day of incubation was similar to that reported by Cunha-Santino et al (2010) for refractory fractions of E. azurea (t 1/2 = 385 to 462 days) in the laboratory. Taylor and Bärlocher (1996) analyzed leaching from dry leaves at room temperature and fresh leaves from different tree species and found that leaf drying had various effects, such as an increase in mass loss due to leaching for most species, leaching reduction for some species or no measurable effect for others.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Analysis of the percent mass loss of E. azurea observed in this study reveals that its decomposition ratio was very slow in comparison to others reported in the literature (Pagioro and Thomaz 1998, Stripari and Henry 2002, Padial and Thomaz 2006, Martins et al 2011, Bianchini Jr. et al 2014. In contrast, the half-life (t 1/2 = 468 days) calculated up to the 35 th day of incubation was similar to that reported by Cunha-Santino et al (2010) for refractory fractions of E. azurea (t 1/2 = 385 to 462 days) in the laboratory. Taylor and Bärlocher (1996) analyzed leaching from dry leaves at room temperature and fresh leaves from different tree species and found that leaf drying had various effects, such as an increase in mass loss due to leaching for most species, leaching reduction for some species or no measurable effect for others.…”
Section: Discussionsupporting
confidence: 85%
“…Dissolved oxygen is another important controlling factor of macrophyte decomposition (Bianchini Jr. et al 2010 and. The oxidation and decomposition of labile fractions of Pistia stratiotes were greater with high availability of oxygen in the water (Bianchini Jr. et al 2010), such as happened with the refractory fractions of E. azurea (Cunha-Santino et al 2010, Bianchini Jr. et al 2014. Anoxic or low oxygenation conditions were not observed in this study, possibly as a result of the presence of a high density of periphytic algae and the proximity to the water surface.…”
Section: Discussionmentioning
confidence: 51%
“…Nevertheless, this species had a low numerical abundance. The contribution of Cyphocharax magdalenae to biomass was probably a sign of the permanent availability of food originating from the pleuston organic matter and the detritus (Azevedo et al, 2008;Neiff et al, 2009;Santino et al, 2010;Casco et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Photosynthesis and primary production of macrophytes have an additional indirect role for freshwater functioning. For example, great amounts of the carbon accumulated by the primary production of macrophytes enters the detritus food web in the form of dissolved organic matter, which is used by microorganisms involved in the microbial loop (Wehr et al, 1999;Farjalla et al, 2006;Cunha-Santino & Bianchini Junior, 2002;Cunha-Santino et al, 2010;Bianchini Junior et al, 2014). This is the quantitatively dominant route of energy in wetlands and shallow lakes, and even if this carbon does not reach higher trophic levels, it fuels the microbial food webs necessary for nutrient cycling in these ecosystems (Wetzel, 1995).…”
Section: Supporting Servicesmentioning
confidence: 99%